2000
DOI: 10.1002/1521-2254(200009/10)2:5<326::aid-jgm133>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac functional improvement by a human Bcl-2 transgene in a mouse model of ischemia/reperfusion injury

Abstract: Bcl-2 overexpression is effective in reducing myocardial reperfusion injury and improving heart function. This benefit correlates with a reduction of cardiomyocyte apoptosis. The apoptotic component of ischemia/reperfusion injury could therefore constitute a new therapeutic target in the acute phase of myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(101 citation statements)
references
References 28 publications
(33 reference statements)
6
93
0
2
Order By: Relevance
“…The present results confirmed this report and demonstrated that a moderate hypercholesterolemia (2% cholesterol diet for 8 weeks) also increased myocardial apoptosis. Several studies stated that inhibition of apoptosis by a variety of pharmacological and genetic approaches results in smaller infarction (Brocheriou et al, 2000;Mocanu et al, 2001) and improved cardiac function (Abbate et al, 2002;Chatterjee et al, 2003). Taurine, is known as to protect various disorders and has been demonstrated to have beneficial effects in nephropathy, cardiomyopathy and neuropathy, (Szymanski and Winiarska, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The present results confirmed this report and demonstrated that a moderate hypercholesterolemia (2% cholesterol diet for 8 weeks) also increased myocardial apoptosis. Several studies stated that inhibition of apoptosis by a variety of pharmacological and genetic approaches results in smaller infarction (Brocheriou et al, 2000;Mocanu et al, 2001) and improved cardiac function (Abbate et al, 2002;Chatterjee et al, 2003). Taurine, is known as to protect various disorders and has been demonstrated to have beneficial effects in nephropathy, cardiomyopathy and neuropathy, (Szymanski and Winiarska, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, both inhibiting apoptosis protein Bcl-2 and promoting apoptosis protein Bax have been extensively studied at present, but their function is still unclear. Brocheriou et al [5] reported a signifi cant reduction of infarct size and cardiomyocyte apoptosis in transgenic mice after pmyocardial ischemia-reperfusion, overexpressing anti-apoptotic human Bcl-2 in cardiomyocyte. In transgenic mice with human Bcl-2 transcripts other than in nontransgenic mice with myocardial ischemia-reperfusion, Chen et al [6] found a significant functional recovery of the heart, small infarct sizes (52.4%), and few apoptotic positive myocytes, accompanied by a three-fold decrease in lactate dehydrogenase (LDH).…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that genetic modification of the myocardium with the anti-apoptotic human Bcl-2 gene conferred myocardial protection against ischemia/reperfusion-induced apoptosis [34,35]. Furthermore, several studies have reported a reduction of apoptosis by ischemic preconditioning via altering the expression of Bcl-2 and/or Bax protein, thus increased the ratio of Bcl-2/Bax protein in preventing the progression of apoptosis in myocardium after ischemia and reperfusion [20,21].…”
Section: Discussionmentioning
confidence: 99%